Secondary chondrosarcoma of the iliac bone in a young woman – a rare case report and review of the literature - David, Therese; Narla, Swetha Lakshmi; Subramanyan, Annapurneswari; N., Kathiresan (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Chondrosarcomas are malignant cartilage-forming tumors, with secondary cases rarely arising from osteochondromas. This report presents a case of secondary chondrosarcoma developing from an undiagnosed pelvic osteo chondroma in a young female, emphasizing the importance of early detection and timely intervention. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. A 28-year-old woman with hip and back pain underwent magnetic resonance imaging, revealing a le sion in the left iliacus muscle with sacroiliac extension. Biopsy confirmed a chondroid neoplasm, and positron emission topog raphy-computed tomography showed minimal metabolic activity. Due to the extensive soft tissue component and recurrence risk, wide local excision was performed. Histology confirmed well-differentiated secondary chondrosarcoma, WHO grade 1 arising from an undiagnosed pre-existing osteochondroma. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The described case highlights the critical role of radiological and histopathological evaluation, timely surgical in tervention, and multidisciplinary management for optimal patient outcomes.